Neural correlates of improvements in personality and behavior following a neurological event. (August 2020) - King, Marcie L.; Manzel, Kenneth; Bruss, Joel; Tranel, Daniel
Abstract: Research on changes in personality and behavior following brain damage has focused largely on negative outcomes, such as increased irritability, moodiness, and social inappropriateness. However, clinical observations suggest that some patients may actually show positive personality and behavioral changes following a neurological event. In the current work, we investigated neuroanatomical correlates of positive personality and behavioral changes following a discrete neurological event (e.g., stroke, benign tumor resection). Patients (N = 97) were rated by a well-known family member or friend on five domains of personality and behavior: social behavior, irascibility, hypo-emotionality, distress, and executive functioning. Ratings were acquired during the chronic epoch of recovery, when psychological status was stabilized. We identified patients who showed positive changes in personality and behavior in one or more domains of functioning. Lesion analyses indicated that positive changes in personality and behavior were most consistently related to damage to the bilateral frontal polar regions and the right anterior dorsolateral prefrontal region. These findings support the conclusion that improvements in personality and behavior can occur after a neurological event, and that such changes have systematic neuroanatomical correlates. Patients who showed positive changes in personality and behavior following a neurological event were rated as having more disturbed functioning prior to the event. Our study may be taken as preliminary evidence that improvements in personality and behavior following a neurological event may involve dampening of (premorbidly) more extreme expressions of emotion. Highlights: Evidence for improvement in personality and behavior following a neurological event. Improvement related to frontal polar and anterior dorsolateral prefrontal damage. Both lesion location and premorbid functioning contribute to improvements.